R-T-B series sintered magnets

The method addresses the challenge of maintaining high coercivity and remanent magnetization in R-T-B sintered magnets by controlling Pr and Ga diffusion and optimizing RLL and oxygen content, achieving high Br and HcJ with reduced Tb usage.

CN111739704BActive Publication Date: 2025-04-25PROTERIAL LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202010199666.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-09-27
Filing Date
2020-03-20
Publication Date
2025-04-25
Estimated Expiration
2040-03-20

AI Technical Summary

Technical Problem

R-T-B sintered magnets face challenges with reduced coercivity (HcJ) at high temperatures, and existing methods to enhance HcJ through rare earth element substitution lead to decreased remanent magnetization (Br), particularly with limited and volatile supply of elements like Tb.

Method used

A manufacturing method for R-T-B sintered magnets that reduces Tb usage while maintaining high Br and HcJ by controlling the diffusion of Pr and Ga through the adjustment of RLL and oxygen content, ensuring Tb concentration gradients within the magnet, and employing specific thermal treatments.

Benefits of technology

The method achieves R-T-B sintered magnets with Br above 1.47 T and HcJ above 1900 kA/m, effectively reducing Tb usage while maintaining high magnetic properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN111739704B_ABST
    Figure CN111739704B_ABST
Patent Text Reader

Abstract

The present invention aims to provide a method for reducing the amount of Tb used and having a high B r and high H cJ The present invention provides a method for manufacturing an R-T-B system sintered magnet. The solution provided by the present invention is an R-T-B system sintered magnet having a residual magnetic flux density (B r ) is 1.47T or more, and the coercive force (H cJ ) is 1900 kA / m or more, and contains Tb, and the Tb content is 0.35 mass% or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an R-T-B system sintered magnet. Background Art

[0002] R-T-B sintered magnets (R is at least one of the rare earth elements, T is mainly Fe, and B is boron) are known to be the highest performance magnets among permanent magnets. They are used in various motors such as voice coil motors (VCM) for hard disk drives, motors for electric vehicles (EV, HV, PHV, etc.), motors for industrial machinery, and home appliances.

[0003] R-T-B series sintered magnets mainly contain R2T 14 The main phase of the B compound and the grain boundary phase located at the grain boundary of the main phase. 14 B compound is a ferromagnetic material with high saturation magnetization and anisotropic magnetic field, which constitutes the basis of the characteristics of R-T-B sintered magnets.

[0004] R-T-B system sintered magnets have a coercive force H at high temperature. cJ (hereinafter referred to as “H cJ Therefore, in particular, R-T-B sintered magnets used in electric vehicle motors are required to have high H even at high temperatures. cJ , that is, a higher H cJ .

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: International Publication No. 2007 / 102391

[0008] Patent Document 2: International Publication No. 2018 / 143230 Summary of the invention

[0009] Technical problem to be solved by the invention

[0010] It is known that R2T 14 When the light rare earth elements RL (mainly Nd and Pr) in the B-type compound phase are replaced by heavy rare earth elements RH (mainly Tb and Dy), H cJ However, in H cJ On the other hand, the improvement will make R2T 14 The saturation magnetization of the B-type compound phase is reduced, so there is a residual magnetic flux density B r (hereinafter referred to as "B rIn addition, due to the limited amount of Tb resources and the limited production areas, there are problems such as unstable supply and price fluctuations. Therefore, it is necessary to avoid using Tb as much as possible (minimize the amount used) and suppress B r of the decrease, and obtain high H cJ .

[0011] Patent Document 1 describes a method of supplying RH to the surface of a sintered magnet of an R-T-B alloy while diffusing RH into the interior of the sintered magnet. In the method described in Patent Document 1, RH is diffused from the surface of an R-T-B alloy sintered magnet into the interior. cJ The outer shell of the main phase grains can effectively increase the RH concentration, thereby suppressing the B r of the decrease, and obtain high H cJ .

[0012] Patent document 2 describes a method for diffusing RL and Ga together with RH from the surface of the R-T-B system sintered raw material through the grain boundary into the interior of the magnet. The method described in patent document 2 can greatly promote the diffusion of RH into the interior of the magnet, reduce the amount of RH used, and obtain extremely high RH. cJ .

[0013] However, in recent years, particularly in electric vehicle motors, there is a demand for lowering RH, and among these, in particular, reducing the amount of Tb used, and obtaining a higher B r and higher H cJ .

[0014] In various embodiments of the present invention, a method for reducing the amount of Tb used and having a high B r and high H cJ A method for producing an R-T-B sintered magnet.

[0015] Technical solutions for solving technical problems

[0016] In the exemplary embodiment of the present invention, the residual magnetic flux density (B r ) is 1.47T or more, and the coercive force (H cJ ) is 1900 kA / m or more, and contains Tb, and the Tb content is 0.35 mass% or less.

[0017] In one embodiment, RL is contained (RL is at least one of the light rare earth elements and must contain Nd and Pr), and when the RL content (mass%) is set to [RL] and the oxygen content (mass%) is set to [oxygen], 26.5mass%≤([RL])-6×[oxygen]≤28.8mass%.

[0018] In one embodiment, the magnet includes a portion where the Tb concentration gradually decreases from the magnet surface toward the inside of the magnet.

[0019] In one embodiment, the magnet comprises a portion where the Pr concentration gradually decreases from the magnet surface toward the inside of the magnet.

[0020] In one embodiment, the Ga concentration gradually decreases from the surface of the magnet toward the inside of the magnet.

[0021] In one embodiment, the Tb content is 0.30 mass % or less.

[0022] In one embodiment, when the oxygen content (mass %) is represented by [oxygen], 0.01 mass % ≤ [oxygen] ≤ 0.15 mass %.

[0023] Effects of the Invention

[0024] According to the embodiments of the present invention, it is possible to provide a device having a high B and a reduced Tb usage. r and high H cJ A method for producing an R-T-B sintered magnet. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1A This is a cross-sectional view schematically showing an enlarged portion of an R—T—B based sintered magnet.

[0026] Figure 1B For the general Figure 1A A cross-sectional view further enlarged and schematically shown within the dashed rectangular area.

[0027] Figure 2 This is a flow chart showing an example of the steps in the method for producing an RTB system sintered magnet according to the present invention.

[0028] Explanation of symbols

[0029] 12…Contains R2T 14 B main phase of compound, 14... grain boundary phase, 14a... two-grain boundary phase, 14b... triple grain boundary phase DETAILED DESCRIPTION

[0030] First, the basic structure of the R-TB system sintered magnet according to the present invention is described. The R-TB system sintered magnet has a structure in which powder particles of a raw material alloy are bonded by sintering. 14 The B compound particles are composed of a main phase and a grain boundary phase located in the grain boundary portion of the main phase.

[0031] Figure 1A This is a cross-sectional view schematically showing an enlarged portion of an R-T-B system sintered magnet. Figure 1B For the general Figure 1A A cross-sectional view further enlarged and schematically shown within the dashed rectangular area. Figure 1A As an example, for reference, an arrow with a length of 5 μm is recorded as a length representing a reference of size. Figure 1A and Figure 1B As shown in the figure, R-T-B sintered magnets are mainly composed of R2T 14 The main phase 12 of the B compound and the grain boundary phase 14 located at the grain boundary portion of the main phase 12 are composed. In addition, in the grain boundary phase 14, Figure 1B As shown, contains 2 R2T 14 The two-grain boundary phase 14a adjacent to the B compound grains (grains) and the three R2T 14 The grain boundary triple point 14b where the B compound particles are adjacent. The typical main phase crystal grain size is 3 μm or more and 10 μm or less in terms of the average value of the equivalent circle diameter of the magnet cross section. 14 B compounds are ferromagnetic materials with high saturation magnetization and anisotropic magnetic field. Therefore, in R-T-B system sintered magnets, by increasing the R2T 14 The presence ratio of B compound can increase r To improve R2T 14 The existence ratio of B compound makes the amount of R, T and B in the raw alloy close to R2T 14 The stoichiometric ratio of compound B (R amount: T amount: B amount = 2:14:1) is sufficient.

[0032] As described above, for example, in Patent Document 2, RL (especially Pr) and Ga are diffused together with RH (for example, Tb) from the surface of the R-T-B system sintered raw material (the surface of the R1-T-B system sintered magnet raw material in the present invention) through the grain boundary into the interior of the magnet. This allows Tb to diffuse greatly into the interior of the magnet, thereby obtaining an extremely high H cJ However, the inventors of the present invention have found that by diffusing Pr and Ga into the interior of the magnet, the width of the two-grain boundary phase becomes wider, which may reduce the volume ratio of the main phase and cause B r Therefore, the inventors of the present invention conducted further research and found that although in order to greatly promote the diffusion of Tb and obtain high H cJThe diffusion of Pr and Ga is effective, but the diffusion amount of Pr and Ga needs to be kept to the minimum. In addition, since Pr and Ga diffuse from the surface of R1-TB system sintered magnet through the grain boundary, it is considered whether the diffusion amount of Pr and Ga into the magnet can be controlled by controlling the grain boundary (the amount and size of grain boundary) in the raw material of R1-TB system sintered magnet. As a result of research based on these insights, it was discovered that by adjusting the RLL (RLL is at least one of the light rare earth elements and must contain Nd) and oxygen content contained in the R1-T-B system sintered magnet raw materials, when the RLL content (mass%) is set to [RLL] and the oxygen content (mass%) is set to [oxygen], the range is 26.3mass%≤[RLL]-6×[oxygen]≤28.6mass%, and when Pr and Ga are diffused into the R1-T-B system sintered magnet raw materials together with Tb, Pr and Ga can be prevented from excessively diffusing into the interior of the magnet and Tb can be greatly diffused.

[0033] The residual magnetic flux density (B r ) is 1.47T or more, and the coercive force (H cJ ) is 1900 kA / m or more, and the Tb content is 0.35 mass% or less (preferably the Tb content is 0.30 mass% or less), which can reduce the amount of Tb used and has an extremely high B r and extremely high H cJ In addition, the amount of RL (RL is at least one of the light rare earth elements and must contain Nd and Pr) in the R-T-B system sintered magnet (after diffusion) at this time, when the RL content (mass%) is set to [RL] and the oxygen content (mass%) is set to [oxygen], is in the range of 26.5mass%≤[RL]-6×[oxygen]≤28.8mass%.

[0034] Among them, B of R-T-B sintered magnet r and H cJThe magnetic properties refer to the magnetic properties of the magnet as a whole, and can be measured, for example, using a B-H tracer. When the magnet is large and the magnetic properties of the magnet as a whole cannot be measured, for example, the corner (end) of the magnet can be processed into a 7 mm square (7 mm × 7 mm × 7 mm) and measured using a B-H tracer. In addition, when the magnet is small, multiple magnets can be stacked into a 7 mm square and measured using a B-H tracer. In addition, the above-mentioned Tb content, the above-mentioned RL content, and the above-mentioned oxygen content refer to the composition (average composition) of the magnet as a whole. Regarding the content of Tb and RL, for example, the high-frequency inductively coupled plasma emission spectrometry (ICP-OES) can be used to measure the magnet as a whole. In addition, regarding the oxygen content, for example, a gas analyzer using a gas fusion-infrared absorption method can be used for measurement.

[0035] (R-T-B sintered magnet)

[0036] The R-T-B system sintered magnet of the present invention contains Tb, and the content of Tb is 0.35 mass% or less (preferably 0.30 mass% or less). In addition, the R-T-B system sintered magnet of the present invention includes a portion where the Tb concentration gradually decreases from the surface of the magnet to the inside of the magnet, a portion where the Pr concentration gradually decreases from the surface of the magnet to the inside of the magnet, and a portion where the Ga concentration gradually decreases from the surface of the magnet to the inside of the magnet. The portion where the concentrations of Tb, Pr and Ga gradually decrease from the surface of the magnet to the inside of the magnet means that Tb, Pr and Ga are in a state of diffusing from the surface of the magnet to the inside of the magnet. Regarding "the portion where the concentrations of Tb, Pr and Ga gradually decrease from the surface of the magnet to the inside of the magnet", it can be confirmed by, for example, performing a line analysis (linear analysis) from the surface of the magnet to the vicinity of the center of the magnet in any cross-section of the R-T-B system sintered magnet using energy dispersive X-ray spectroscopy (EDX). Regarding the concentrations of Tb, Pr and Ga, the concentrations will be determined based on the location of the measurement in the main phase grains (R2T 14 B compound particles) or at the grain boundaries, or the R1-T-B system sintered magnet raw materials before diffusion, or the types and presence of compounds containing Tb, Pr and Ga produced during diffusion, there are local decreases or increases in the concentration of Tb, Pr and Ga, respectively. But overall, the concentrations of Tb, Pr and Ga gradually decrease as they go into the interior of the magnet (the concentration gradually decreases). Therefore, even if there is a local decrease or increase in concentration, as long as the overall amount of Tb, Pr and Ga gradually decreases from the surface of the magnet to the inside of the magnet at a depth of at least 200μm, it belongs to the "portion where the concentration of Tb, Pr and Ga gradually decreases from the surface of the magnet to the inside of the magnet" of the present invention.

[0037] In addition, the R-T-B system sintered magnet of the present invention contains RL (RL is at least one of the light rare earth elements, and must contain at least one of Nd and Pr). When the content (mass%) of RL is set to [RL] and the content (mass%) of oxygen is set to [oxygen], 26.5mass%≤[RL]-6×[oxygen]≤28.8mass% is satisfied. Hereinafter, "[RL]-6×[oxygen]" is sometimes referred to as "R'". When the above R' is less than 26.5mass%, Tb, Pr and Ga are difficult to diffuse from the surface of the magnet to the inside of the magnet, and H cJ It is possible to reduce; when it exceeds 28.8mass%, Tb, Pr and Ga diffuse excessively from the surface of the magnet to the inside of the magnet, B r It is possible to reduce. Preferably, the above R' is 27.0 mass% or more and 28.0 mass% or less (27.0 mass% ≤ [RL] - 6 × [oxygen] ≤ 28.0 mass%). This can have a higher B r and higher H cJ In addition, the content (mass%) of RL is 90 mass% or more of the total content of R. When the content of RL is less than 90 mass% of the total content of R, B r It is possible to reduce.

[0038] The residual magnetic flux density (B r ) is above 1.47T, the coercive force (H cJ ) above 1900kA / m, while reducing the amount of Tb used, it has a very high B r and very high H cJ .

[0039] The R-T-B system sintered magnet has, for example, the following composition.

[0040] R: 26.8 mass% or more and 31.5 mass% or less (R is at least one of the rare earth elements, including Tb and RL, and the content of RL is 90 mass% or more of the total content of R);

[0041] B: 0.80mass% or more and 1.20mass% or less;

[0042] M: 0.05 mass% to 1.0 mass% (M is at least one selected from Ga, Cu, Zn and Si);

[0043] M1: 0 mass% or more and 2.0 mass% or less (M1 is at least one selected from Al, Ti, V, Cr, Mn, Ni, Zr, Nb, Mo, Ag, In, Sn, Hf, Ta, W, Pb and Bi);

[0044] the remainder T (T is Fe or Fe and Co); and inevitable impurities.

[0045] Among them, RL is a light rare earth element and must contain Nd and Pr. In addition, the content of Nd and Pr in RL is preferably 90 mass% or more of the total content of RL. Light rare earth elements include La, Ce, Nd, Pr, Pm, Sm, Eu, etc. In addition, as unavoidable impurities, O (oxygen), N (nitrogen), C (carbon), etc. can be listed, but in order to obtain higher B r and H cJ When the oxygen content (mass %) is defined as [oxygen], it is preferred that 0.01 mass % ≤ [oxygen] ≤ 0.15 mass %.

[0046] The R—T—B based sintered magnet preferably satisfies the following formula (1) when the content (mass %) of T is [T] and the content (mass %) of B is [B].

[0047] [T] / 55.85>14×[B] / 10.8 (1)

[0048] Satisfying the formula (1) means that the content of B is less than R2T 14 The stoichiometric composition ratio of the B compound, i.e., the ratio of the B compound to the compound used to form the main phase (R2T 14 The amount of T in the B compound is relatively small. By satisfying formula (1), a higher H cJ .

[0049] The method for producing the R-T-B system sintered magnet of the present invention is as follows, for example Figure 2 As shown, it includes: step S10 of preparing R1-TB system sintered magnet raw material; step S20 of preparing R2-Ga alloy; step S30 of making at least a part of R2-Ga alloy contact with at least a part of the surface of R1-TB system sintered magnet raw material, performing a first heat treatment at a temperature of 700°C to 950°C in a vacuum or inert gas atmosphere, thereby diffusing R2 and Ga into the magnet raw material; step S40 of performing a second heat treatment at a temperature of 450°C to 750°C and lower than the temperature of the first heat treatment in a vacuum or inert gas atmosphere on the R-TB system sintered magnet after the first heat treatment. The following is an explanation.

[0050] In the present invention, the RTB system sintered magnet before and during diffusion is referred to as "R1-TB system sintered magnet raw material", and the RTB system sintered magnet after diffusion is simply referred to as "RTB system sintered magnet".

[0051] (Process of preparing raw materials for R1-T-B system sintered magnets)

[0052] First, the composition of the R1-TB based sintered magnet raw material will be described.

[0053] The R1-T-B system sintered magnet raw material of the present invention is characterized in that the RLL (RLL is at least one of the light rare earth elements and must contain Nd) and oxygen content contained in the R1-T-B system sintered magnet raw material are adjusted. Specifically, when the content (mass%) of RLL is set to [RLL] and the content (mass%) of oxygen is set to [oxygen], it is set to the range of 26.3mass%≤[RLL]-6×[oxygen]≤28.6mass%. By subjecting such R1-T-B system sintered magnet raw material to the diffusion process described later, Pr and Ga will not diffuse excessively into the interior of the R1-T-B system sintered magnet raw material, and the diffusion of Tb can be greatly carried out.

[0054] The R1-T-B system sintered magnet raw material has the following composition, for example.

[0055] R1: 26.6 mass% or more and 31.3 mass% or less (R1 is at least one of the rare earth elements, including RLL, and the content of RLL is 90 mass% or more of the total content of R1);

[0056] B: 0.80mass% or more and 1.20mass% or less;

[0057] M: 0 mass% or more and 1.0 mass% or less (M is at least one selected from Ga, Cu, Zn and Si);

[0058] M1: 0 mass% or more and 2.0 mass% or less (M1 is at least one selected from Al, Ti, V, Cr, Mn, Ni, Zr, Nb, Mo, Ag, In, Sn, Hf, Ta, W, Pb and Bi);

[0059] the remainder T (T is Fe or Fe and Co); and inevitable impurities.

[0060] Among them, RLL is a light rare earth element and must contain Nd. In addition, the content of Nd in RLL is preferably 80 mass% or more of the entire RLL. Light rare earth elements include La, Ce, Nd, Pr, Pm, Sm, Eu, etc. In addition, as unavoidable impurities, O (oxygen), N (nitrogen), C (carbon), etc. can be listed, but in order to obtain a higher B r and H cJ When the oxygen content (mass %) is defined as [oxygen], it is preferred that 0.01 mass % ≤ [oxygen] ≤ 0.15 mass %.

[0061] In the R1-T-B based sintered magnet material, when the content (mass %) of T is [T] and the content (mass %) of B is [B], it is preferred that the following formula (1) is satisfied.

[0062] [T] / 55.85>14×[B] / 10.8 (1)

[0063] Satisfying the formula (1) means that the content of B is less than R2T 14 The stoichiometric composition ratio of the B compound, i.e., the ratio of the B compound to the compound used to form the main phase (R2T 14 The amount of T in the B compound is relatively small. By satisfying formula (1), a higher H cJ .

[0064] Next, the preparation method of the raw material of the R1-T-B system sintered magnet is described. The raw material of the R1-T-B system sintered magnet can be prepared by a general manufacturing method of the R-T-B system sintered magnet represented by the Nd-Fe-B system sintered magnet. For example, the raw material alloy produced by the strip casting method or the like is crushed into 3 μm or more and 10 μm or less using a jet mill or the like, and then formed in a magnetic field, and sintered at a temperature of 900°C or more and 1100°C or less, thereby preparing it.

[0065] The particle size of the raw material alloy (volume center value obtained by measurement using air flow dispersion laser diffraction method = D 50 When the particle size is less than 3 μm, it is very difficult to prepare the pulverized powder, and the production efficiency is greatly reduced, which is not preferred. On the other hand, when the pulverized particle size exceeds 10 μm, the crystal particle size of the R-T-B system sintered magnet finally obtained is too large, and it is difficult to obtain a high H cJ As long as the above conditions are met, the R1-TB system sintered magnet raw material can be made from one raw material alloy (single raw material alloy) or by mixing two or more raw material alloys (blending method).

[0066] (Step of Preparing R2-Ga Alloy)

[0067] First, the composition of the R2-Ga alloy will be described.

[0068] R2 in the R2-Ga alloy is at least two of the rare earth elements, and must contain Tb and Pr. Preferably, R2 is 65 mass% or more and 97 mass% or less of the entire R2-Ga alloy, and Ga is 3 mass% or more and 35 mass% or less of the entire R2-Ga alloy. The content of Tb in R2 is preferably 3 mass% or more and 24 mass% or less of the entire R2-Ga alloy. In addition, the content of Pr in R2 is preferably 65 mass% or more and 86 mass% or less of the entire R2-Ga alloy. In addition, less than 50 mass% of Ga can be replaced with at least one of Cu and Sn. R2-Ga alloy may contain unavoidable impurities. Among them, "less than 50% of Ga can be replaced with Cu" in the present invention means that when the content (mass%) of Ga in the R2-Ga alloy is set to 100%, 50% of it can be replaced with Cu. Preferably, the content of Pr in the R2-Ga alloy is 50 mass% or more of the entire R2, and more preferably, R2 is composed only of Pr and Tb. By containing Pr, diffusion in the grain boundary phase becomes easier, so Tb can be diffused more efficiently, and a higher H cJ .

[0069] The shape and size of the R2-Ga alloy are not particularly limited and may be any. The R2-Ga alloy may be in the form of a film, foil, powder, block, pellet, or the like.

[0070] Next, a method for preparing the R2-Ga alloy will be described.

[0071] The R2-Ga alloy can be prepared by a raw material alloy preparation method generally used in the production method of R-T-B system sintered magnets, such as mold casting, strip casting, single roll super quenching method (melt spinning method), atomization method, etc. In addition, the R2-Ga alloy can also be a material obtained by pulverizing the alloy obtained above using a known pulverizing device such as a pin mill.

[0072] (Diffusion process)

[0073] The following diffusion process is performed, i.e., at least a portion of the above-mentioned R2-Ga alloy is brought into contact with at least a portion of the surface of the R1-T-B system sintered magnet raw material prepared as described above, and a first heat treatment is performed at a temperature of 700°C to 950°C in a vacuum or inert gas atmosphere, thereby causing R2 and Ga to diffuse into the interior of the magnet raw material. As a result, a liquid phase containing Tb, Pr and Ga is generated from the R2-Ga alloy, and the liquid phase is diffused and introduced from the surface of the sintered raw material to the interior through the grain boundaries in the R1-T-B system sintered magnet raw material. At this time, it is preferred to increase the content of RH contained in the R1-T-B system sintered magnet raw material to an extremely small amount in the range of 0.05 mass% to 0.35 mass%. The extremely high HcJ Improved effect. In order to increase the Tb content contained in the R1-TB system sintered magnet raw material by 0.05 mass% or more and 0.35 mass% or less, various conditions such as the amount of R2-Ga alloy, the heating temperature during treatment, the particle size (when the R2-Ga alloy is in granular form), and the treatment time can be adjusted. Among these, by adjusting the amount of R2-Ga alloy and the heating temperature during treatment, the amount of RH introduced (increased amount) can be controlled relatively easily. In addition, in this specification, "increasing the Tb content by 0.05 mass% or more and 0.35 mass% or less" means that in the content expressed in mass%, its numerical value increases by 0.05 or more and 0.35 or less. For example, when the Tb content of the R1-TB system sintered magnet raw material before the diffusion process is 0.50 mass% and the Tb content of the R-TB system sintered magnet after the diffusion process is 0.60 mass%, the Tb content is increased by 0.10 mass% through the diffusion process. In addition, whether the content of at least one of Tb and Dy (RH amount) is increased by 0.05 mass% or more and 0.35 mass% or less can be confirmed by measuring the Tb content in the R1-TB system sintered magnet raw material before the diffusion process and the R-TB system sintered magnet after the diffusion process (or the R-TB system sintered magnet after the second heat treatment) as a whole, and finding how much the Tb content is increased before and after the diffusion. In addition, when there is a concentrated portion of the R2-Ga alloy on the surface of the R-TB system sintered magnet after the diffusion (or the surface of the R-TB system sintered magnet after the second heat treatment), the RH amount is measured after removing the concentrated portion by cutting or the like.

[0074] When the first heat treatment temperature is lower than 700°C, the amount of liquid phase containing Tb, Pr and Ga is too small to obtain high H cJ On the other hand, when the temperature exceeds 950℃, H cJ It is possible to reduce the temperature. It is preferably 850°C or higher and 950°C or lower. This can obtain a higher H cJ In addition, it is preferred that the R-TB system sintered magnet after the first heat treatment (700°C to 950°C) is cooled from the temperature at which the first heat treatment was performed to 300°C at a cooling rate of 5°C / min or more. This can obtain a higher H cJ The cooling rate to 300° C. is more preferably 15° C. / min or more.

[0075] The first heat treatment can be performed by configuring an R2-Ga alloy of any shape on the surface of the R1-TB system sintered magnet raw material using a known heat treatment device. For example, the surface of the R1-TB system sintered magnet raw material can be coated with a powder layer of the R2-Ga alloy to perform the first heat treatment. For example, a slurry in which the R2-Ga alloy is dispersed in a dispersion medium can be applied to the surface of the R1-TB system sintered magnet raw material, and then the dispersion medium is evaporated to bring the R2-Ga alloy into contact with the R1-TB system sintered magnet raw material. Among them, alcohols (ethanol, etc.), aldehydes, and ketones can be exemplified as dispersion media. In addition, RH can be introduced not only from the R2-Ga alloy, but also by configuring the fluoride, oxide, oxyfluoride, etc. of RH together with the R2-Ga alloy on the surface of the R-TB system sintered magnet to introduce RH. That is, as long as RL and Ga can be diffused simultaneously with RH, the method is not particularly limited. Examples of the fluoride, oxide, and oxyfluoride of RH include TbF 3 , DyF 3 , Tb 2 O 3 , Dy 2 O 3 , Tb 4 OF, and Dy 4 OF.

[0076] In addition, regarding the R2-Ga alloy, as long as at least a portion of the R2-Ga alloy contacts at least a portion of the R1-T-B system sintered magnet raw material, its configuration position is not limited, and it is preferred to configure the R2-Ga alloy to contact at least the surface of the R1-T-B system sintered magnet raw material perpendicular to the orientation direction. This allows the liquid phase containing R2 and Ga to diffuse and introduce from the surface of the magnet to the inside more efficiently. In this case, the R2-Ga alloy can be contacted only in the orientation direction of the R1-T-B system sintered magnet raw material, or the entire surface of the R1-T-B system sintered magnet raw material can be contacted with the R2-Ga alloy.

[0077] (Step of Implementing Second Heat Treatment)

[0078] The R1-TB system sintered magnet raw material after the first heat treatment is heat treated in a vacuum or inert gas atmosphere at a temperature of 450°C to 750°C, which is lower than the temperature in the step of performing the first heat treatment. In the present invention, this heat treatment is referred to as the second heat treatment. By performing the second heat treatment, a high H cJ When the temperature of the second heat treatment is higher than the temperature of the first heat treatment, or when the temperature of the second heat treatment is lower than 450°C or higher than 750°C, high H may not be obtained. cJ .

[0079] Example

[0080] Experimental Example 1

[0081] The raw materials of each element are weighed so that the raw materials of the R1-T-B series sintered magnets have approximately the composition shown in No. A to G in Table 1, and the alloy is made by strip casting. The obtained alloys are coarsely pulverized by hydrogen pulverization to obtain coarse pulverized powder. Next, 0.04 mass% of zinc stearate is added to the obtained coarse pulverized powder as a lubricant relative to 100 mass% of the coarse pulverized powder. After mixing, an air flow pulverizer (jet mill device) is used to dry pulverize in a nitrogen flow to obtain a pulverized particle size D 50 A finely pulverized powder (alloy powder) of 4 μm. To the finely pulverized powder, 0.05 mass% of zinc stearate is added as a lubricant relative to 100 mass% of the finely pulverized powder. After mixing, the mixture is molded in a magnetic field to obtain a molded body. Among them, the molding device uses a so-called right-angle magnetic field molding device (horizontal magnetic field molding device) in which the direction of magnetic field application is orthogonal to the direction of pressure application. The obtained molded body is sintered in a vacuum at a temperature of not less than 1060°C and not more than 1090°C (a temperature that can fully densify by sintering is selected for each sample) for 4 hours to obtain an R1-T-B system sintered magnet raw material. The density of the obtained R1-T-B system sintered magnet raw material is 7.5Mg / m 3 The above. The results of the composition of the obtained R1-TB system sintered magnet raw material are shown in Table 1. Among them, each component in Table 1 was measured using high-frequency inductively coupled plasma emission spectrometry (ICP-OES). In addition, the O (oxygen) content was measured using a gas analyzer using a gas fusion-infrared absorption method. Among them, each component is the result of the composition of the entire R1-TB system sintered magnet raw material (the average composition of the entire magnet). The following results are the same for the composition of the R2-Ga alloy and the R-TB system sintered magnet. In addition, the value of [RLL]-6×[oxygen] in the R1-TB system sintered magnet raw material is shown in Table 1. Among them, the experimental examples other than No.F and No.G (No.A~E) are all within the preferred range of the present invention (26.3mass%≤[RLL]-6×[oxygen]≤28.6mass%).

[0082] [Table 1]

[0083]

[0084] The raw materials of each element are weighed so that the R2-Ga alloy roughly becomes the composition shown in No.a of Table 2, and these raw materials are dissolved to obtain a strip or flake alloy by a single roll superquenching method (melt spinning method). The obtained alloy is crushed in an argon atmosphere using a mortar, and then passed through a sieve with a mesh of 425μm to prepare an R2-Ga alloy. The composition of the obtained R2-Ga alloy is shown in Table 2. Among them, each component in Table 2 is measured using high-frequency inductively coupled plasma optical emission spectrometry (ICP-OES).

[0085] [Table 2]

[0086]

[0087] The R1-T-B system sintered magnet raw materials No.A to G in Table 1 were cut and ground into cubes of 7.4 mm × 7.4 mm × 7.4 mm. Next, the R1-T-B system sintered magnet raw materials were spread on the entire surface of the R1-T-B system sintered magnet raw materials No.A to G under the diffusion conditions shown in Table 3. No.3 in Table 2 indicates that 2 mass% of R2-Ga alloy (No.a) was spread on 100 mass% of the R1-T-B system sintered magnet raw materials No.B. In addition, No.3 indicates that the same diffusion process was performed twice. Therefore, in No.3, a total of 4 mass% was spread. The same is also recorded in No.1 to 2 and No.4 to 10. In the diffusion process, the first heat treatment was performed at 900°C for 4 hours in a reduced pressure argon controlled at 50 Pa, and then cooled to room temperature. Thus, the R-T-B system sintered magnet after the first heat treatment was obtained. Furthermore, the R-T-B system sintered magnet after the first heat treatment was subjected to a second heat treatment at 480°C for 3 hours in a reduced pressure argon controlled at 50 Pa, and then cooled to room temperature to produce R-T-B system sintered magnets (No. 1 to 10). The amount of Tb, RL (Nd + Pr in the case of this example), the amount of oxygen, and R' ([RL] - 6 × [oxygen]) in the obtained R-T-B system sintered magnet are shown in Table 3. In addition, the obtained R-T-B system sintered magnet was subjected to mechanical processing, and the sample was processed into 7mm × 7mm × 7mm, and the measurement was performed using a BH tracer. The measurement results are shown in Table 3. In addition, the results of line analysis (linear analysis) from the magnet surface to the vicinity of the magnet center of the magnet cross section of No. 1 to 10 using EDX confirmed that in all samples, the concentrations of Tb, Pr and Ga gradually decreased (the concentrations gradually became lower) as they went from the magnet surface to the magnet center.

[0088] [Table 3]

[0089]

[0090] As shown in Table 3, the present invention examples all obtained B r 1.47T or more, H cJ High B above 1900kA / m r and high H cJ In contrast, the comparative examples No. 9 and 10, in which R′ was out of the range of the present invention, did not obtain B r 1.47T or more, H cJ High B above 1900kA / mr and high H cJ .

[0091] Example 2

[0092] R1-TB system sintered magnets were produced in the same manner as in Example 1 except that the raw materials of each element were weighed so that the raw materials of R1-TB system sintered magnets had approximately the compositions shown in No. H to No. P in Table 4. The composition of the raw materials of R1-TB system sintered magnets obtained is shown in Table 4.

[0093] [Table 4]

[0094]

[0095] R2-Ga alloy was prepared in the same manner as in Example 1 except that the raw materials of each element were weighed so that the R2-Ga alloy had substantially the composition shown in No. b and c in Table 5. The composition of the obtained R2-Ga alloy is shown in Table 5.

[0096] [Table 5]

[0097]

[0098] The R1-TB system sintered magnet raw materials No. H to P in Table 4 were cut and ground into cubes of 7.4 mm × 7.4 mm × 7.4 mm, and then diffused in the same manner as in Example 1 under the diffusion conditions shown in Table 6. Among them, the R1-TB system sintered magnet raw materials No. H to P were diffused with the R2-Ga alloy No. b, and the R1-TB system sintered magnet raw material No. H was diffused with the R2-Ga alloy No. c. Furthermore, the diffusion process (first heat treatment) and the second heat treatment were also carried out in the same manner as in Example 1 to obtain R-TB system sintered magnets (No. 11 to 20). The amount of Tb, RL, oxygen content, and R′ ([RL]-6×[oxygen]) in the obtained R-TB system sintered magnets are shown in Table 6. In addition, the obtained R-T-B system sintered magnet was machined to a size of 7 mm × 7 mm × 7 mm, and the sample was measured using a BH tracer. The measurement results are shown in Table 6. In addition, EDX was used to perform line analysis (linear analysis) from the magnet surface to the vicinity of the center of the magnet in the cross section of No. 11 to 20. The results confirmed that in all samples, as the concentration of Tb, Pr and Ga gradually decreased (the concentration gradually became lower) from the magnet surface to the center of the magnet.

[0099] [Table 6]

[0100]

[0101] As shown in Table 6, the examples of the present invention all obtained Br 1.47T or more, H cJ High B above 1900kA / m r and high H cJ .

[0102] Industrial Applicability

[0103] According to the present invention, a sintered RTB magnet having high residual magnetic flux density and high coercivity can be produced. The sintered magnet of the present invention is suitable for various motors such as motors for hybrid vehicles and household electrical appliances that are exposed to high temperatures.

Claims

1. An R-T-B system sintered magnet, characterized in that: Mainly containing R2T 14 The main phase of the B compound particles and the grain boundary phase located at the grain boundary portion of the main phase are composed of The residual magnetic flux density B of the R-T-B system sintered magnet r 1.47T or more, coercive force H cJ is 1900 kA / m or more, and contains Tb, wherein the content of Tb is 0.30 mass% or less, The R-T-B system sintered magnet contains RL, which is at least one of the light rare earth elements and must contain Nd and Pr. When the content (mass%) of RL is [RL] and the content (mass%) of oxygen is [oxygen], 26.5mass%≤([RL])-6×[oxygen]≤28.8mass%, and 0.07mass%≤[oxygen]≤0.15mass%, The R-T-B system sintered magnet includes: a portion where the Tb concentration gradually decreases from the magnet surface to the inside of the magnet; a portion where the Pr concentration gradually decreases from the magnet surface to the inside of the magnet; and a portion where the Ga concentration gradually decreases from the magnet surface to the inside of the magnet.

Citation Information

Patent Citations

  • R-Fe-B RARE EARTH SINTERED MAGNET AND METHOD FOR PRODUCING SAME

    WO2007102391A1

  • Rare-earth sintered magnet and method for manufacturing same

    CN104737244A

  • Method for producing R-T-B system sintered magnet

    CN107077965A

  • R-t-b based permanent magnet

    CN108154988A

  • R-t-b sintered magnet

    CN109478452A